Bioethics training needs assessment for HIV research in vulnerable populations: a survey of trainees at college of health sciences, Makerere university - Josephine Nayiga; Stephen Okoboi; Grace Banturaki; Pauline Byakika-Kibwika; Barbara Castelnuovo (BMC Medical Ethics)
Abstract Background Research involving vulnerable populations of people living with HIV (PLWH), such as children, adolescents, older adults, pregnant and lactating women, hospitalized patients, and key populations, presents complex bioethical challenges. We assessed bioethics training needs for trainees engaged in HIV research from the School of Medicine (SoM) of Makerere University and the Infectious Disease Institute (IDI) to inform the development of a comprehensive bioethics training program for trainees. Methods A cross-sectional quantitative study was conducted from March to May 2024 using an online structured questionnaire distributed via Google Forms. Participants included former and current trainees who have conducted research with PLWH within the past five years. Data collected included self-rated bioethics knowledge, frequency of encountering bioethical challenges, confidence in addressing challenges across vulnerable populations, and preferred training topics and delivery formats. Descriptive data analysis was performed using STATA Version 17. Results We attained a response rate of 67.5% (108/160). While 75.9% reported formal bioethics training, 58.3% rated their knowledge moderate. Frequently encountered challenges included maintaining confidentiality and privacy (61.1%), conducting informed consent processes (56.1%), applying bioethical principles, engaging with communities (54.6%), and selecting appropriate research participants (51.4%). Confidence in addressing bioethical challenges was notably lower for vulnerable populations than for general HIV research. Confidence of the trainees was higher in research involving older PLWH and pregnant/lactating women, moderate with children/adolescents and hospitalized individuals, and very low with key populations. Trainees expressed limited confidence in addressing cultural sensitivity, stigma, coercion, community engagement, harm monitoring, and compensation for research-related harm across all the populations. Top training priorities included ethical issues with research involving vulnerable populations (97.2%), reporting ethical concerns (94.4%), community engagement (93.6%), research on stored samples/data (94.5%), and stigma/discrimination (92.6%). Preferred formats were in-person workshops, interactive case-based scenarios, and online courses. Conclusion Trainees faced diverse bioethical challenges and exhibited varying confidence levels in addressing these issues across different vulnerable populations. These findings underscore the need for targeted, context-specific bioethics training tailored to conducting research with vulnerable PLWH. This study has informed the development of a comprehensive training program to improve the ethical conduct of HIV research in Uganda. Clinical trial number Not applicable.